KONTRIBUSI DAYA LEDAK OTOT LENGAN-BAHU DAN KOORDINASI MATA-TANGAN TERHADAP KETEPATAN SMASH DALAM PERMAINAN TENIS MEJA PADA SISWA SMAN 5 KETAMPUTIH KECAMATAN BENGKALIS - Herwan Saputra; Slamet Slamet; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, research problem is the low ability athletes smash Students SMAN 5 Ketamputih District of Bengkalis that are not exactly on target and often out of the table. To view the possible factors that predicted low capacity explosive power smash arm muscles and hand-eye coordination, then conducted a study that aims to determine how much contribution the explosive power arm muscles and hand-eye coordination to the accuracy of table tennis athletes smash Students SMAN 5 Ketamputih Subdistrict Bengkalis. This type of research is correlational. The population is all table tennis athletes Students SMAN 5 Ketamputih Bengkalis District of active practice and samples were taken with total sampling technique with a number of 15 athletes. Data was collected using measurment against three variables. For suspended explosive power arm muscles using the medicine ball test, using a hand-eye coordination test caught throwing a tennis ball against the wall, and accuracy using test accuracy smash smash fore hand and backand. Data analysis technique used is the product moment correlation and multiple correlation. The result showed that there are 1) contribution to the arm muscle explosive power smash accuracy, with a correlation coefficient of 0.753 rhitung> rtabel 0.514 and the value of determination of 0.567 means explosive power arm muscles contribute 56.70% to smash accuracy, 2) there is a contribution of coordination eyes hand to smash accuracy rhitung 0.809> 0.514 rtabel and the value of determination of 0.6545 means that the hand-eye coordination contributed 65.45% to the accuracy smash, 3) explosive power and hand-eye coordination made to contribute to the accuracy and value of 0,82 smash determination and Fhitung 11.33 0.6724> 3.88 Ftabel hand-eye coordination means to contribute to smash 67.24% accuracy. It is suggested to related parties such as coaches, athletes, and official attention to these two factors so that the precision of the athletes smash Students SMAN 5 Ketamputih District of Bengkalis can be improved.Keywords : Explosive Power of the arm and shoulder muscles, Smash, Table Tennis